Government Education Expenditures, Pre-Primary Education and School Performance: A Cross-Country Analysis - Daniela Del Boca; Chiara Monfardini; Sarah Grace See (Institute of Labor Economics (IZA), 2018)
Using data from OECD's PISA, Eurostat and World Bank's WDI, we explore how child cognitive outcomes at the aggregate country level are related to macroeconomic conditions, specifically government education expenditures and early education experience. We find that both government expenditures in education and attendance to early child care are associated with better later school performance. We also consider different childcare characteristics such as duration and quality, which appear to have significant effects Our results may imply that policies encouraging childcare expansion should also take into account quality issues.
Keywords: I26; 330; early childcare and education; school performance; test scores